Pengalaman, Brand Attitude, dan FoMo pada Perilaku Pembelian Impulsif Generasi Z Saat Berbelanja Online - Qurniawati, Rina Sari; Indriastuti, Adelia; Nurohman, Yulfan Arif (Jurnal Manajemen Dayasaing, 2025)
This study aims to examine and explain online customer shopping behavior, attitudinal loyalty, FoMO towards impulsive buying. The number of samples in this study was 160 respondents who were generation Z who had Shopee accounts in Central Java. The analysis technique used was Path Analysis using SmartPLS version 3. The results showed that online customer shopping behavior influenced attitudinal loyalty and impulsive buying and FoMO influenced impulsive buying. Meanwhile, attitudinal loyalty was not proven to influence impulsive buying and did not mediate the relationship between OSCE and impulsive buying. Theoretically, this study contributes to the literature related to OSCE, attitudinal loyalty, FoMO, and impulsive buying. For Managers, this study emphasizes shopping ethics when consumers buy online.